Formulation and Physical Characterization of Onion (Allium ascalonicum L) Bulb Extract in Cream Using Tween 80 and Span 60 as the Emulgator - Fauzia Ningrum Syaputri; Vinda Maharani Patricia (Jurnal Sains dan Kesehatan, 2019)
In Indonesia, it is not uncommon to find children who suffer from fever which can occur due to the change of weather from the rainy season during the dry season or vice versa. Communities in rural areas generally use onion (Allium ascalonicum L) to relieve fever in children. Cream preparations are made by varying the concentration of the emulgator to determine the effect of different concentrations of the emulgator on the physical characteristics of the cream preparation. The emulgator used is tween 80 and span 60 with a concentration of Formula 1: 3.5%, Formula 2: 3.75%, formula 3: 4%. Physical evaluations carried out in this study were organoleptic, pH, homogeneity, cream washability, cream type, viscosity, spreadability, adhesion, and freeze-thaw tests. The results of the study it can be concluded that the differences in the concentration of the emulgator can affect the physical characteristics of the cream preparation, namely in the spreading test and the adhesion test shows that F3 (4%) can reduce the spreadability of the cream preparation but can be attached to a long time when compared to F1 (3.5%) and F2 (3.75%). The physically optimal cream preparation formula is F1 and F2 because it meets all the requirements in the evaluation test. Keywords: Cream, onion, emulgator, physical characteristics